The determinants of non-tariff barriers in Malaysia’s agricultural sector - Hanif, Azlina; Alavi, Rokiah; Duasa, Jarita; Mat Ghani, Gairuzazmi (Faculty of Business and Management, Universiti Teknologi MARA Terengganu, 2011)
The successive rounds of multilateral trade negotiations have resulted in significant tariff reductions in many countries. Malaysia is no exception as the applied most-favoured-nation tariff rate in her agricultural sector in 2009 is relatively low, averaging at 2.8 percent.Despite the reduction in tariff barrier, the incidence of non-tariff barriers (NTBs) in the sector over the 1978–2007 period has generally increased even though efforts at dismantlin these barriers have long been initiated. Thus, the paper seeks to identify factors that influence the level of NTBs in the agricultural sector. Using the autoregressive distributed lag (ARDL) approach to cointegration, we find imports, average tariff, sectoral competitiveness level, and employment growth to be significant determinants of NTBs in the agricultural sector. The findings provide a greater understanding of the reasons behind agricultural trade protectionism.